Study on Motives Underlying the Buying of Fast Fashion in India Despite Associated Sustainability Issues - Sushil Kumar Bishnoi; Ramratan Guru (Tekstilec, 2024)
The purpose of this study was to identify motivational factors for consumers in making a purchase decision for a fast fashion product. The term fast fashion is used to refer to cheaper replicas of luxury fashion trends. Apart from impacting the environment adversely, fast fashion has several other issues as well. Fast fashion has many sustainability issues but its demand is growing at a tremendous pace. The motives for the preference for fast fashion were explored in this study. Both primary and secondary data were used to conduct this research. The primary data was collected for this study via questionnaire. All the factors are rated on the 7-point Likert scale. Furthermore, the laddering technique of interviewing was employed to investigate the underlying values. The study revealed that “creating self-identity” is the most influencing motive for consumers in making a purchase decision for a fast fashion product, while “showing dominance” is the least influencing motive for consumers in making a purchase decision for a fast fashion product. This study offers insight into the factors influencing buying decisions for a fast fashion product. This research can help address the issue of sustainability in the fashion industry. These findings can also be used to promote sustainable fashion.